Control strategy comparison of the 8/6 switched reluctance motor in several inverter topologies - Martua, Ronaldo; Emir, Alam Raihan; Suhendra, Michael; Yesayevtta, Denri; Rizqiawan, Arwindra; Furqani, Jihad (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This paper proposes a control strategy for switched reluctance motors (SRMs) using the asymmetric half-bridge (AHB), shared switch, and Miller converter based on MATLAB/Simulink and TMS320F28379D. The control strategy implemented in this study involves the application of proportional-integral (PI) speed control with a pulse width modulation (PWM) switching method for each topology. By employing this control strategy, the system aims to regulate the speed of the motor and achieve the desired performance while ensuring efficient power utilization. The PI controller is utilized to adjust the motor's speed based on the error between the desired and actual speeds, enabling precise control. Additionally, the PWM switching method is employed to modulate the motor voltage, allowing for smooth and continuous speed adjustments. A thorough method for maximizing each topology's performance and raising the overall system efficiency is provided by this combination of control techniques. The detailed analysis and operation of each converter are presented in this paper. Simulation and experiment results show that AHB and shared switch have better performance than Miller. But the Miller converter needs the least number of switching components. Although the performance of the shared switch is equal to that of AHB, uses of this topology are limited to SRM with an even number of phases.